Adherence to antihypertensive medications among adult hypertensive patients attending chronic follow-up units of Dessie Referral Hospital, Northeastern Ethiopia: A cross-sectional study. Issue 31 (6th August 2021) - Andualem, Atsedemariam; Liknaw, Tiliksew; Edmealem, Afework; Gedefaw, Mihretie
Abstract : Abstract: Hypertension is the leading cause of increased morbidity and mortality rates worldwide. Despite adherence to therapies is the important determinant of treatment success to reduce apparent resistant hypertension, maintaining good adherence to antihypertensive medications remained the most serious challenge. Thus, this study aimed to assess adherence to antihypertensive medications among adult hypertensive patients in Dessie Referral Hospital. A cross-sectional study design was conducted among hypertensive patients during May and June 2020. The study participants were selected using a systematic random sampling technique. The collected data were entered into EpiData version 4.4 and exported to SPSS version 25.0 software for data cleaning and analysis. Data were analyzed using bivariable and multivariable logistic regression at a 95% confidence interval (CI). A variable that has a P -value < .05 was declared as statistically significant. Hosmer–Lemeshow test was used to test goodness-of-fit and multicollinearity was tested. The overall good adherence to antihypertensive medications was 51.9%; 95% CI: (46.8–58.3%) and poor adherence was 48.1%. Factors associated with good adherence were: sex— female adjusted odd ratio (AOR) = 1.31; 95% CI (1.06– 2.52), occupational status- employed AOR = 2.24; 95% CI (1.33– 3.72), good knowledge of the disease AOR = 2.20; 95% CI (1.34– 3.72) and good self-efficacy AOR = 1.38; 95% CI (1.20– 2.13). This study revealed that almost half of the hypertensive patients in Dessie Referral Hospital had good antihypertensive medication adherence. Sex, occupational status, knowledge, and self-efficacy were factors associated with good adherence. Therefore, health education should be given to patients on the importance of complying with medication and patients should be monitored by health extension workers.